A meta‐analysis of oceanic DMS and DMSP cycling processes: Disentangling the summer paradox. Issue 4 (28th April 2015) - Galí, Martí; Simó, Rafel
Abstract The biogenic volatile compound dimethylsulfide (DMS) is produced in the ocean mainly from the ubiquitous phytoplankton osmolyte dimethylsulfoniopropionate (DMSP). In the upper mixed layer, DMS concentration and the daily averaged solar irradiance are roughly proportional across latitudes and seasons. This translates into a seasonal mismatch between DMS and phytoplankton biomass at low latitudes, termed the "DMS summer paradox, " which remains difficult to reproduce with biogeochemical models. Here we report on a global meta‐analysis of DMSP and DMS cycling processes and their relationship to environmental factors. We show that DMS seasonality reflects progressive changes in a short‐term dynamic equilibrium, set by the quotient between gross DMS production rates and the sum of biotic and abiotic DMS consumption rate constants. Gross DMS production is the principal driver of DMS seasonality, due to the synergistic increases toward summer in two of its underlying factors: phytoplankton DMSP content (linked to species succession) and short‐term community DMSP‐to‐DMS conversion yields (linked to physiological stress). We also show that particulate DMSP transformations (linked to grazing‐induced phytoplankton mortality) generally contribute a larger share of gross DMS production than dissolved‐phase DMSP metabolism. The summer paradox is amplified by a decrease in microbial DMS consumption rate constants toward summer. However, this effect is partially compensated by a concomitant increase in abiotic DMS loss rate constants. Besides seasonality, we identify consistent covariation between key sulfur cycling variables and trophic status. These findings should improve the modeling projections of the main natural source of climatically active atmospheric sulfur.